Analysis Of Al-Aṣīl And Al-Dakhil Interpretation Of The Story Of Prophet Solomon's Trial QS. Ṣād In Tafsir Al-Ṭabarī - Himayah, Dewi Malihatil; Qomariyah, Qomariyah; Khoiroh, Muflikhatul; Lestari, Annisa Putri Wahyu (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2024)
Tafsir Ja>mi' al-Baya>n 'an Takwi>l Al-Qur’a>n by Ibn Jari>r al-Tabari> is a bi al-ma'thu>r tafsir book that is often used as a reference by other bi al-ma'thu>r tafsir books. But in his interpretation, al-Tabari> uses a lot of isra>i>li>yya>>>t history. In fact, not all isra>i>liyya>>t history can be accepted and used as a reference. History of isra>i>li>yya>>>t that contradicts religious law is rejected as a reference in interpreting the Qur'an. Therefore, this study aims to analyze the infiltration contained in al-Tabari's interpretation of the story of the test of Prophet Solomon in QS. This research method uses a descriptive-analytical approach with the theory of al-asi>l wa al-dakhi>l. The results of this study indicate the infiltration (dakhi>l) carried out by al-Tabari>> when interpreting surah Sa>d 34. In his interpretation, he cites isra>i>li>yya>>>t history which states that the test of Prophet Solomon is that Satan has taken the ring which is the source of Prophet Solomon's strength and changed himself to resemble Prophet Solomon. This narration clearly contradicts Islamic shari'a because it is impossible for Satan to resemble the form of the Prophet who is an awake human being or ma'su>m.